Performansi Analisis Algoritma Koloni Semut (Ant Colony Optimization) dalam menyelesaikan permasalahan Capacitated Vehicle Routing Problem (CVRP) - Izza Hasanul Muna (Universitas Sarjanawiyata Tamansiswa, 2022)
The ant colony algorithm (ACO) is an algorithm initially introduced by Moyson and Manderick and then developed by Marco Dorigo. This algorithm has been applied in various optimization problems, like in the Capacitated Vehicle Routing Problem (CVRP). The aim of this study was to investigate the performance of the ACO in solving CVRP. ACO will be measured based on 3 factors, memory usage, execution time and accuracy level. Moreover, identification of the effect of changing parameter on ACO performance was also carried out. The result shows that ACO has good performance in solving CVRP in all of 3 factors. However, the performance of ACO was influenced by several parameters. The findings in the study indicate that there are several ACO parameters that have a significant effect on ACO performance, there are the number of ants, , and . For the others, Q dan , both of them do not have significant effect on the performance of ACO in terms of time execution and memory usage. For parameter , it has significant effect on the result produced by ACO.